Effect of climate and habitat on morphological characteristics and fruit production of Picralima nitida (Stapf) in West Africa - Akabassi, Ghislain Comlan; Padonou, Elie Antoine; Gbesso, Gbodja Houéhanou François; Assogbadjo, Achille Ephrem; Zirihi Guede, Noël (Journal of Environmental Geography, 2023)
Picralima nitida is an important African medicinal plant species used in pharmaceutical industries and traditional medicine to treat several diseases. Despite its importance, the species faces conservation problem. This study evaluated the effect of climate and habitat on morphological characteristics and fruit production of P. nitida. A total of 132 fruiting trees was randomly sampled from three habitat types (home gardens, botanical garden and natural forest) and three soils (Nitisols, Arenosols and Acrisols) in Dahomey Gap and Guineo-Congolese zone. A total of 5 morphological traits and fruit production were recorded per tree to describe the relationship between morphological determinism of the species and climate. Pearson correlation was performed to identify the suitable habitat type in each climatic zone. Harmonized World Soil Database was used to determine physicochemical characteristics of the soil types on which the species occurred. Results revealed that the climatic zones (p<0.001) and habitat types (p<0.0001) inﬂuenced signiﬁcantly the morphological characteristics and fruit production of P. nitida. High trees with more number of fruits were observed in home gardens on acid soils (Nitisols (pH: 5) and Arenosols (pH: 5.3)) in Dahomey Gap. In Guineo-Congolese zone, the species was more present in natural forest on acid Acrisols (pH: 5).